People purchase intention towards hydrogen fuel cell vehicles: An experiential enquiry in Malaysia. (30th January 2016) - Al-Amin, Abul Quasem; Ambrose, Angelina F.; Masud, Muhammad Mehedi; Azam, Mohammad Nurul
Abstract: Hydrogen fuel cell vehicles (FCVs) are expected to have a significant impact in meeting both energy security and environmental concerns globally. Public and private support is however essential for successful transition to a sustainable energy system. Several studies have looked into the issues and considered the purchase behaviour of related Alternative Fuel Vehicles (AFCs) and more research momentum is seen towards hydrogen FCV. The article aims to critically review and identifies gaps of acceptance, preferences and attitudes of hydrogen FCV and examine whether attitudes, subjective norms (SNs) and perceived behaviour control (PBC) have significant associations with customer purchase intention (PI) and purchase behaviour of hydrogen FCV in Malaysia. This is a timely study to address useful policies for decarbonizing the transportation sector. Highlights: Hydrogen fuel cell vehicle (FCV) has the potential to meet both energy security and environmental concerns globally. Significance of attitudes, subjective norms, perceived behaviour control with purchase intention and purchase behaviour. Concern about the environment may not drive purchase behaviour of hydrogen FCV.